Big Dataphenomenology: Embodied Big Data - Kappler, Karolin Eva (AoIR Selected Papers of Internet Research, 2016)
Pursuing the current problem of (not) making sense of Big Data and the fruitless efforts to detect its value, the paper proposes a phenomenological view on Big Data. In a reflection on enriched, small, big, thick, and raw data, it introduces the distinction between body and embodiment (in German: Körper and Leib), following the phenomenological tradition of perception and thinking of corporeality. By this, it denunciates the missing depth and context in current (digital) data assemblages, suggesting the concept of Embodied Big Data.